To mention or not to mention? The inclusion of self-reported most traumatic and most positive memories in the life story. Issue 2 (7th February 2022) - Kongshøj, Inge Lise Lundsgaard; Bohn, Annette; Berntsen, Dorthe
ABSTRACT: Many theories on Posttraumatic Stress Disorder (PTSD) make assumptions on the relationship between PTSD and centrality of traumas to the life story and identity. Although the Centrality of Event Scale (CES) is a popular measure of centrality of personally experienced events to the life story, no studies have examined whether self-rated "central" events are mentioned, when individuals recount their lives. It is also unknown if mentioning specific event types in the life story is related to psychological health or life story coherence. We asked 386 adults to write their life stories, nominate their most traumatic and positive events, rate these events on the CES, and complete measures of PTSD and depression. Two-thirds of the sample mentioned at least one event, with the positive event being mentioned twice as often as the trauma. Mentioned events were more central than non-mentioned events. Participants who mentioned their trauma scored higher on symptoms of PTSD and depression than participants who only mentioned their positive event, but did not write less coherent life stories. Further, death- and illness-related traumas were mentioned more often than accidents and disasters. Findings are discussed in relation to theories on trauma memory in PTSD.